Anaesthesia, Pain, Intensive Care and Emergency Medicine - A.P.I.C.E. Proceedings of the 12th Postgraduate Course in Critical Care Medicine Trieste, Italy - November 19–21, 1997 - Gullo, Antonino (Springer Milan, 1998)
The management of critically ill patients has,in the past few years, been a discipline at the forefront of development which continues to make progress with the support of basic and clinical research in the broadest sense. The application of biotechnology in this particular area has revealed itself to be essential in an attempt to provide the best interpretation of the bio-humoral and functional alterations present in a long series of often complex clinical conditions. The care of the critically ill is also at the forefront in the application of increasingly sophisticated clinical monitoring systems that also contribute to standardizing certain procedures, establish guidelines, and evaluate the efficacy of therapeutic interventions and their costs
Keywords: Emergency Medicine; Anesthesiology; Intensive / Critical Care Medicine; Emergency medicine; Critical care medicine; Intensivtherapie; Anästhesie; Schmerztherapie; Notfalltherapie; Konferenzschrift -- 1997 -- Triest